Pelvic Inflammatory Disease: Possible Catches and Correct Management in Young Women - Chiara Di Tucci; Daniele Di Mascio; Michele Carlo Schiavi; Giorgia Perniola; Ludovico Muzii; Pierluigi Benedetti Panici (Case Reports in Obstetrics and Gynecology)
The incidence of adnexal masses increases exponentially with age and the most frequent causes in young women are physiologic cysts and pelvic abscesses with pelvic inflammatory disease (PID). Clinical examination can direct physicians to an appropriate management of adnexal mass, but the role of transvaginal ultrasound is crucial for diagnosis and treatment decision, even if it sometimes can be misleading, especially in young women. Ca 125, blood count, and CRP are useful to clarify suspected etiology of a pelvic mass, but specificity and positive predictive value are low because elevation of laboratory tests may occur in several benign conditions. In our work we present four cases of suspected pelvic masses. Despite guidelines for management of PID, the right timing to switch to surgical therapy is not clear. Therefore, the treatment decision should be based on a careful evaluation of various parameters such as signs symptoms and above all age. Moreover, we believe that, for a correct diagnosis and for the best fertility sparing treatment, it is also extremely important to refer to a gynecological oncology unit with an expert surgeon.